Strategi Dakwah Melalui Integrasi Sosial: Asimilasi Budaya Melayu di Ma’had Aman Bistari Selangor Malaysia - Khodijah, Dewi; Isnaini; Mohd Asri bin Yunus (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
The phenomenon of religious conversion in Malaysia, particularly among new Muslim students at Ma'had Aman Bistari who come from Chinese, Indian, and indigenous backgrounds, poses challenges to social integration and the formation of religious identity. This study aims to formulate a strategic da'wah model rooted in Malay culture to support inclusive integration. Using a qualitative case study approach, data were collected through interviews, observations, and documentation of da'wah activities. Thematic analysis revealed four key aspects of integration: social participation through community dialogue, adoption of Malay cultural symbols, horizontal relationships based on empathy, and spiritual and economic empowerment. The findings emphasize that strategic da'wah is inseparable from the socio-cultural dimensions that shape the daily interactions of converts. This study confirms that the da'wah strategy through social integration at Ma'had Tahfidz Vokasional Aman Bistari Selangor is effective in supporting the process of Malay cultural assimilation among students who convert to Islam across ethnicities. The findings indicate that da'wah practices focus not only on spiritual teachings but also on strengthening social cohesion through language, lifestyle, and inclusive cultural interactions.